A dated phylogeny of Argophyllaceae (Asterales) is consistent with spread by long-distance dispersal. Issue 1 (2nd January 2022) - Maurin, Kévin J. L.; Smissen, Rob D.
ABSTRACT: Argophyllaceae is a small eudicot family of trees and shrubs of south-western Pacific distribution, comprising two genera: Corokia and Argophyllum . The phylogeny of Corokia, which contains six species, has attracted little attention so far, the genus being usually represented by a single species in studies looking at relationships at higher taxonomic levels. Here we bridge this knowledge gap with a complete phylogeny of the genus based on whole-plastid DNA sequences. We also investigated nuclear ribosomal DNA markers, which yielded a poorly supported phylogeny. Comparing fossil-calibrated and biogeographic dating approaches, we conclude that extant Argophyllaceae species are probably not Gondwanan relicts, the timing of their divergences being better explained by long-distance dispersal after the break-up of Gondwana than by vicariance. The high level of endemicity of the species of Corokia prevents the reconstruction of a precise biogeographic history of the genus, but our phylogenies suggest that the genus originated in Australia, then about 3.5 My ago started dispersing eastwards into the Pacific towards its present-day distribution.